Female Workers, Male Managers: Gender, Leadership, and Risk-Taking - Ulf Rinne; Hendrik Sonnabend (Institute of Labor Economics (IZA), 2019)
This study examines gender differences in risk-taking behavior among managers in a female-dominated industry. Using data from international top-level women's soccer, we provide evidence that male coaches show a lower level of risk-taking than female coaches on average. We also find a U-shaped age effect that is independent of gender, meaning that young and more mature individuals tend to take riskier decisions. Our main results therefore strongly contrast with the majority of previous studies on gender differences in risk preferences, and thereby emphasize the importance of considering the industrial environment. Underlying selection processes may play an important role. We find no correlation between the gender gap in risk-taking and female empowerment defined by national gender equality scores.
Keywords: D81; J16; J4; M12; Z29; 330; gender; risk-taking; leadership; management; female empowerment